2020
DOI: 10.3897/zookeys.981.53583
|View full text |Cite
|
Sign up to set email alerts
|

Genus-level revision of the Alycaeidae (Gastropoda, Cyclophoroidea), with an annotated species catalogue

Abstract: 412 species-group names (including 11 replacement names), and 14 genus-group names of the Alycaeidae have been introduced to date. Type materials of 85% (336) of the known species and subspecies were examined, a further 5% (19) of the taxa were studied using available non-type material, and for another 6% (22) the original descriptions were sufficiently detailed to evaluate their taxonomic status. Only 3% of the taxa (12) could not be examined. Special attention was paid to the sculpture of the embryonic whorl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…Dicharax species inhabiting China, Laos and Vietnam have been revised recently by . Several other species have been included in Dicharax in a recent family-wise revision without examining species-level taxonomy (Páll-Gergely et al 2020b). Here we report a total of ten Dicharax species from Thailand, six out of ten species being recorded from their type localities only, and the remaining species with additional occurrences within the vicinity of the type locality which ranges wider within Thailand or both Thailand and Myanmar.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Dicharax species inhabiting China, Laos and Vietnam have been revised recently by . Several other species have been included in Dicharax in a recent family-wise revision without examining species-level taxonomy (Páll-Gergely et al 2020b). Here we report a total of ten Dicharax species from Thailand, six out of ten species being recorded from their type localities only, and the remaining species with additional occurrences within the vicinity of the type locality which ranges wider within Thailand or both Thailand and Myanmar.…”
Section: Discussionmentioning
confidence: 99%
“…The alycaeid shell is complicated mostly due to the three clearly distinguishable regions of the teleoconch (R1, R2, R3) having their own characteristics of sculpture (the most important is the rib density), length and morphology. Previous revisions , 2020b, Páll-Gergely and Auffenberg 2019 showed that most populations are recognizable, i.e. possess unique combinations of characters that distinguish them from other conspecific populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dicharax caudapiscis Páll-Gergely & Hunyadi, 2018 and D. stuparum Páll-Gergely & Hunyadi, 2018 were described from Northern Thailand subsequently (Páll-Gergely and Hunyadi 2018). Following the genus definition of , as many as 164 nominal species were assigned to Dicharax, including three Alycaeus species that were formerly recorded from Thailand or "Siam", namely A. davisi Godwin-Austen, 1914, A. omissus Godwin-Austen, 1914, and A. pratatensis Panha & Burch, 1997(Páll-Gergely et al 2020b.…”
Section: Introductionmentioning
confidence: 99%